Fatal fulminant myocarditis and multiorgan failure following accidental Cassia occidentalis ingestion in a child: A case report and review of literature (Indian Journal of Case Reports, 2026)
Cassia occidentalis (Coffee Senna) is a toxic leguminous weed widely distributed across tropical and subtropical regions, including rural India, where accidental ingestion by children continues to pose a serious but underrecognized public health threat. Its seeds contain potent anthraquinone derivatives and toxalbumins that disrupt mitochondrial oxidative phosphorylation, leading to a fulminant multiorgan syndrome encompassing hepatic failure, rhabdomyolysis, toxic encephalopathy, and myocarditis. We report the case of a 4-year-old previously healthy child who presented to the pediatric intensive care unit 2 days after the accidental ingestion of C. occidentalis seeds, with progressive vomiting, lethargy, and hemodynamic instability. Clinical examination revealed hypotension, tachycardia, tachypnea, drowsiness, and hepatomegaly. Electrocardiography revealed ST-segment elevations in multiple leads, and echocardiography confirmed severe left ventricular systolic dysfunction with an ejection fraction of 25%, consistent with fulminant myocarditis. Despite aggressive intensive care management, including mechanical ventilation, inotropic support with dopamine and adrenaline, fresh frozen plasma transfusions and vitamin K. The child deteriorated rapidly and succumbed within 12 h of admission due to refractory cardiogenic shock and multiorgan failure. This case highlights the fulminant and near-universally fatal course of C. occidentalis toxicity when cardiac involvement occurs and underscores the critical need for early suspicion, prompt referral to tertiary pediatric critical care facilities, and robust community education campaigns for prevention in endemic rural areas.